Differential gene expression of oil palm (Elaeis guineensis jacq.) fruits during late ripening stages and molecular characterisation of metallothionein-like transcripts - Salim Al-Shanfari, Ahmed Bakhit (2012)
Oil palm (Elaeis guineensis Jacques) is a major oil crop of economic importance in the world. Different biological and physiological mechanisms occur during oil palm fruit ripening. These mechanisms are regulated by the genes expressed during fruit ripening processes. Therefore, determining the structure and function of the expressed genes involved in these mechanisms will help to improve the important characters for enhancing palm fruit oil yield and quality. A forward suppression subtractive hybridization (SSH) library was constructed to identify genes involved in fruit ripening in oil palm. Oil deposition, as an oil palm fruit ripening indicator, will start at approximately 12 weeks after anthesis (w.a.a.) with an active period of oil synthesis at 15-16 w.a.a. until fruit maturity at about 20 w.a.a. in the mesocarp. Hence, the suppression was performed with cDNA extracted from fruits at 12 w.a.a. as “driver” and fruits at 17 w.a.a. as “tester”. A single-pass sequencing from the 5′-end of 2,112 randomly selected cDNA clones resulted in 2,019 high-quality expressed sequence tags (ESTs). Clustering of the 2,019 EST sequences showed 20 unigenes consisting of 9 contigs and 11 singletons. Among the edited EST sequences, 1,109 (14 unigenes) had significant matches with protein sequences in the public databases. The matched ESTs were further classified into six putative cellular functions including unclassified proteins (38.0%), cell rescue and defense (33.8%), proteins with binding functions (27.7%),biogenesis of cellular component (0.3%), metabolism (0.1%), and cell cycle (0.1%). At 17 w.a.a., the 20 unigenes were expressed at higher abundance compared to 12 w.a.a. Two of the abundant transcripts encoding type 2 metallothionein-like proteins designated as MET2a and MET2b were selected for further study due to their high abundance (16.05%) in the SSH library and their involvement in biological processes in fruit development and maturation. The second part of the present study involved the isolation of the full-length cDNA encoding MET2a and MET2b from the ripening oil palm fruit mesocarp at 17 w.a.a. and examing their expression patterns compared to the other two previously reported type-3 MT members (MT3-A and MT3-B) in various oil palm organs including different vegetative and reproductive tissues. The full-length cDNA sequence of MET2a and MET2b were 571 and 553 bp designated as EgMT2a and EgMT2b, respectively. Their sequences were homologous (67–77%) with several type-2 MTs in plants. All four genes were differentially expressed in the ripening oil palm mesocarp tissues but undetectable in the vegetative tissues examined. All the MT genes examined were significantly up-regulated in the mature developmental stages of oil palm fruit mesocarp except for EgMT2b which was expressed only at 17 w.a.a. but at a much lower level. The type 2 MT-like proteins are more in relation with late fruit ripening stage than the type 3 MT-like proteins consistent with their reported functions in the homeostasis or detoxification. The findings in the present study will contribute to a better understanding of the molecular mechanisms involved in fruit ripening in oil palm.